Oil palm motorized cutter / Mohd Nazmi Hanirer and Bernedict Ready Babu - Hanirer, Mohd Nazmi; Babu, Bernedict Ready (Faculty of Plantation and Agrotechnology, 2023)
Oil Palm Motorized Cutter specially designed for harvesting Fresh Fruit Bunches (FFB) and cutting fronds. After doing the R&D process, this product is based on latest technology which will ease the harvesting and cutting fronds process and reduce the time consumed. The productivity is also equivalent to two to three human harvesters. By using Oil Palm Motorized Cutter from our company, the estate would be able to reduce 50% of its labour requirement in the harvesting operation. Another advantage of this cutter is that the terrain or topography of estate does not restrict its usage. Our target market are small holder and oil palm plantation. We targeted them because our product can help them to do work faster and reduce the time consumed during harvesting and cutting fronds process. In three years, our company might expand our business in producing and improving the Oil Palm Motorized Cutter so that it can be the best product in the market in our country.